2021
DOI: 10.3389/fpsyg.2021.689425
|View full text |Cite
|
Sign up to set email alerts
|

Tinkering With Testing: Understanding How Museum Program Design Advances Engineering Learning Opportunities for Children

Abstract: Using a design-based research approach, we studied ways to advance opportunities for children and families to engage in engineering design practices in an informal educational setting. 213 families with 5–11-year-old children were observed as they visited a tinkering exhibit at a children’s museum during one of three iterations of a program posing an engineering design challenge. Children’s narrative reflections about their experience were recorded immediately after tinkering. Across iterations of the program,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Further, children indicate what causal knowledge they have acquired from their exploration in the course of their reflections, even when tested over long delays (e.g., Marcus et al, 2018). Marcus et al (2021) also showed that children's reflections on their experience at a museum exhibit related to their understanding of the engineering knowledge inherent in that exhibit when children were tested at home a week later.…”
Section: Exploration and Reflection In Museum Settingsmentioning
confidence: 99%
“…Further, children indicate what causal knowledge they have acquired from their exploration in the course of their reflections, even when tested over long delays (e.g., Marcus et al, 2018). Marcus et al (2021) also showed that children's reflections on their experience at a museum exhibit related to their understanding of the engineering knowledge inherent in that exhibit when children were tested at home a week later.…”
Section: Exploration and Reflection In Museum Settingsmentioning
confidence: 99%
“…In this project, families engaged in tinkering in a hands-on manner using familiar and everyday materials they had at home. Tinkering activities that include an engineering design challenge or a problem to be solved have the best potential to support engineering learning, as families have shown increased engagement in engineering talk and practices during these activities (Marcus, Acosta, et al, 2021; Pagano et al, 2020). Therefore, in this study, families had to consider two criteria: the hat had to fit their head, and the hat could not fall off when jumping up and down.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for why the implementation of both function-focused goals and orientations was so important for spatial language in reflections is that engineering-focused programs best engage families in engineering concepts and practices. Function-focused goals engage families in the engineering practice of testing and iterating (Marcus et al, 2021) and orientations explicate engineering principles (Acosta et al, 2021). Spatial thinking and skills underlie these engineering principles and practices (Uttal, Miller, et al, 2013).…”
Section: Tinkering Programsmentioning
confidence: 99%